Role of proton motive force in genetic transformation of Bacillus subtilis. - van Nieuwenhoven, M H (1982)
This study explored the role of the proton motive force in the processes of DNA binding and DNA transport of genetic transformation of Bacillus subtilis 168 strain 8G-5 (trpC2). Transformation was severely inhibited by the ionophores valinomycin, nigericin, and 3,5-di-tert-4-hydroxybenzylidenemalononitrite (SF-6847) and by tetraphenylphosphonium. The ionophores valinomycin and nigericin also severely inhibited binding of transforming DNA to the cell envelope, whereas SF-6847 and carbonylcyanide-p-trifluoromethoxyphenylhydrazone hardly affected binding. The proton motive force, therefore, does not contribute to the process of DNA binding, and valinomycin and nigericin interact directly with the DNA binding sites at the cell envelope. The effects of ionophores, weak acids, and tetraphenylphosphonium on the components of the proton motive force and on the entry of transforming DNA after binding to the cell envelope was investigated. DNA entry, as measured by the amount of DNase I-resistant cell-associated [3H]DNA and by the formation of DNA breakdown products, was severely inhibited under conditions of a small proton motive force and also under conditions of a small delta pH and a high electrical potential. These results suggest that the proton motive force and especially the delta pH component functions as a driving force for DNA uptake in transformation.